Renewable energy resources and technologies practice in Malaysia - Mekhilef, Saad (2010)
Malaysia is endowed with vast renewable energy resources such as biomass and solar. Besides, hydro and wind power can be considered as potential renewable energy resources. Harnessing these resources appears to be a promising solution for improving the life quality of rural villagers. The government and many non-governmental organizations (NGOs) have tried to comprehend and have strived to address the problem of energy. The depleting gas and oil sources is also a problem which the government never took for granted as a number of energy-related policies was proposed since six decades ago to ensure the sustainability and efficiency in energy supply. The overall approach in examining this issue will focus on the ongoing renewable energy projects, energy policies for promoting RE as one of the energy supply, technologies used as well as the future direction of the renewable energy sector. This paper reviews the renewable energy resources and renewable energy technologies (RETs) practicing in Malaysia in terms of its implementation, research and development activities.